Reimagining the Past and Rethinking the Other: The Significance of Creative Historical Revision in Bernardine Evaristo’s The Emperor’s Babe (2001) and Blonde Roots (2008) - Evangeline Scarpulla (Dive-In)
In The Emperor’s Babe (2001) and Blonde Roots (2008), Bernardine Evaristo employs historical revision and counter-discursive narrative techniques to rethink the paradigm of self and Other. At the forefront of contemporary postcolonial feminist literature, Evaristo uses humor and personal stories to address contemporary cultural issues. Her novels challenge Western historical narratives, which have often been constructed to reinforce specific ideologies and structures of power. Evaristo's use of the alternate history or uchronia genre offers a way to reimagine historical moments, particularly those of Roman ruled Britain and the transatlantic slave trade, revealing alternative possibilities and highlighting the experiences of those often erased in traditional historical accounts. Through intersectional feminist close readings, this paper examines how Evaristo subverts epic and utopian narrative structures and questions entrenched notions of race, gender, and identity while providing new ways to understand history and its impact on global social dynamics.